Physics event photo analysis module based on the STEM approach: An effort to enhance critical thinking - Maryani, Maryani; Yuliana, Yasmin; Anggraeni, Firdha Kusuma Ayu (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
This research aimed to determine the validity of the Physics Event Photo Analysis (AFKF) module based on the STEM approach and improve students' critical thinking skillsat SMA Negeri 1 Rogojampi. The researchers implemented the ADDIE development model to achieve these goals, which consisted of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data collecting techniques used in this research were interviews, product validation, and tests. The validation results indicated that the product was feasible to use with a validity percentage of 93%. The percentages can be categorized as very valid and can be used without revision. Furthermore, the percentage of the product's effectiveness in improving students' critical thinking abilitywas 66.58% which was included in the medium category. The PhysBased on the STEM approach, the Event Photo Analysis Module (AFKF) based ed positive responses from students with a percentage of 76%.TThis development research concluded that the STEM approach-based Physics Event Photo Analysis (AFKF) module is very valid and effective in improving students' critical thinking skills.